Texture analysis of starfruit (Averrhoa carambola) chips pre-treated with glucose syrup and osmotic dehydration - Siti Radhiah Omar,; Syafiqah Abdul Razak,; Nur Zazarina Ramly, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Osmotic dehydration (OD) of starfruit chips by glucose syrup was chosen as the osmotic agent (OA) in this study as it is believed to confer a desirable result in the final product. As in this study, the concentration of glucose syrup that was used is 30, 40 and 50°Brix with soaking temperature of 20°C to 60°C and soaking time of 20 min to 60 min. The result showed that higher water loss and lower solid gain of starfruits obtained as the higher temperature and glucose syrup concentrations were used. Meanwhile, processing of osmo-dried starfruits into chips were done by stir frying with canola oil. The use of glucose syrup with concentration of 50°B, 60°C temperature and 60 min soaking time produced the highest hardness and crispness of starfruit chips with the lowest moisture content. Test of significance (p<0.05) in results obtained from this study were determined using Minitab 18 software as one-way Analysis of Variance (ANOVA) and Tukey-Test. In general, OD pre-treatment could be proved as an effective technique for food industries to develop fried starfruit chips with improved texture quality.